Naturalistic hotspots along the Itinerarium Rosaliae (CW Sicily, Italy). Issue 8 (17th November 2018) - Domina, G.; Saporita, P.; Margagliotta, V.; Venturella, G.; Gargano, M. L.
ABSTRACT: The conservation, fruition and management of landscape and natural resources is one of the most important topic of the moment. Here we presented a study on naturalistic hotspots that can be found along the Itinerarium Rosaliae, a naturalistic and religious route in Sicily that crosses three natural reserves and one natural regional park connecting Mount Pellegrino with the Hermitage of Santo Stefano di Quisquina. On the whole 7 semi-natural woods, 13 monumental trees, 8 geosites, and 4 areas of high naturalistic interest were identified. This initiative can be of example for other territories where human and natural heritage can be connected for an organic network of fruition.